The Influence of Digital Self Service and Social Media Promotion on Loyalty with Customer Satisfaction as an Intervening Variable Study on PT PLN (Persero) Customers - Yeni Iryantini; Endang Tjahjaningsih (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This paper aims to analyze the relationship between Digital Self-Service and social media promotion on customer loyalty with customer satisfaction as an intervening variable for PLN Mobile application customers in the UID Banten region. Quantitative with a survey method of 100 PLN Mobile customers in the UID Banten region. Data collection was carried out through a 7-point Likert scale questionnaire, then analyzed using SPSS to test validity, reliability, multiple linear regression, and Sobel mediation test to measure the relationship between variables. The results show that Digital Self-Service and Social Media Promotion have a positive effect on Customer Satisfaction, which then acts as a mediator in forming Customer Loyalty towards PLN Mobile services. The results show that Digital Self-Service and promotion through social media have a positive and significant effect on customer satisfaction. However, both do not have a significant direct effect on customer loyalty. On the contrary, customer satisfaction is proven to significantly influence loyalty, making it a key factor in forming user loyalty towards the PLN Mobile application. In addition, customer satisfaction also plays a significant role as a mediator in the relationship between digital services and promotions with customer loyalty.